1997
DOI: 10.1093/ndt/12.4.713
|View full text |Cite
|
Sign up to set email alerts
|

Thiobarbituric acid reactive substances are increased in the subcutaneous fat tissue of patients with end-stage renal disease

Abstract: This study supports the finding of a severe peroxidative state in patients with end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 8 publications
1
15
1
1
Order By: Relevance
“…Our previous report [2]showed that serum antioxidant activity measured as serum scavenging activity against the hydroxyl radical was decreased in uremic plasma, and this was improved by HD. Moreover, we have shown a tendency for TBARS in subcutaneous fat tissue to decrease after the induction of maintenance HD [5]. From the combination of these results, we conclude that a single session of HD does not influence lipid peroxidation of uremic patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our previous report [2]showed that serum antioxidant activity measured as serum scavenging activity against the hydroxyl radical was decreased in uremic plasma, and this was improved by HD. Moreover, we have shown a tendency for TBARS in subcutaneous fat tissue to decrease after the induction of maintenance HD [5]. From the combination of these results, we conclude that a single session of HD does not influence lipid peroxidation of uremic patients.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study from our group using electron spin resonance indicated that the serum antioxidant activity against the hydroxyl radical is decreased in hemodialysis (HD) patients [2]. We have also demonstrated an improvement in the inhibitory effect of serum on the generation of lipid peroxides in hepatic microsomal NADPH-dependent P-450 reductase [3, 4]and an accumulation of thiobarbituric acid reactive substances (TBARS) in subcutaneous fat tissue in end-stage renal disease (ESRD) patients [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Lipid and protein oxidative markers (TBARS, PC) were significantly increased in HD patients compared to HC. Previous studies have also reported elevated plasma concentrations of lipid peroxidation byproducts and oxidative protein damage in HD patients compared to healthy controls [30,31,32]. In HD patients, lipid peroxidation may be attributed to the formation of advanced glycation end products, even at normal glucose levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown the beneficial effect of vitamin E administration on hemodialysis patients [25], which would occur by lowering the lipid peroxide level, whose elevation was shown to be involved in a variety of diseases [26] including end-stage renal disease. Treatment with citrate has been advocated in patients with hypocitraturia because of its lowering effect on calcium oxalate supersaturation by binding calcium [27].…”
Section: Resultsmentioning
confidence: 99%